Flexure–shear interaction in hybrid steel I-girders at ambient and elevated temperatures - Ghadami, Abbas; Broujerdian, Vahid (Advances in structural engineering, 2019)
In literature, there is no theoretical research focusing on moment–shear interaction behavior of the hybrid girders. This article investigates the moment–shear interaction behavior of non-composite hybrid steel plate I-girders at ambient and elevated temperatures. In this regard, based on a more realistic distribution of bending and shear stresses, theoretical equations have been proposed to achieve the moment–shear interaction curve without considering shear buckling. The results obtained from the proposed equations were compared with the results of the existing experimental data and those of the finite element analysis. According to the results, there is good agreement between them.